EXPLORING UNDERGRADUATE STUDENTS' PERCEPTIONS OF EFL SPEAKING CLASSES: INSIGHTS FROM SIX DIMENSIONS IN INDONESIAN HIGHER EDUCATION - Rosdiana, Ihda; Taufiqulloh, Taufiqulloh (University of Kuningan, 2025)
This study investigates the undergraduate perceptions over EFL speaking classes in six dimensions: general perceptions of speaking classes, anxiety, engagement and motivation, instructional strategies or methods, peer and teacher interactions, and assessment. This study employed a mixed-methods approach. The data were gathered from a 30-item Likert-scale survey questionnaire that was distributed to 40 undergraduate students of English Education Department, Faculty of teacher Training, Universitas pancasakti Tegal in the odd semester of the academic year 2024/2025. Using descriptive statistics and qualitative analysis, the findings indicate that students generally have positive views over the speaking classes attended, particularly valuing the instructional strategies like role plays and group discussions. However, anxiety stemming from fear of judgment and low self-confidence becomes a persistent challenge. In the dimension of engagement and motivation, the level was moderate as the activities linked to real-world situations and goal setting as a crucial part for maintaining interest. The study also highlights the importance of various instructional strategies to cope with varied learner needs, such as integrating technology-based tools like self-recorded videos and topic-specific vlogs. Moreover, peer and teacher interactions contributed a significant role to alleviate anxiety and to encourage communication, while the assessment approaches like peer and collaborative assessments were appreciated for self-reflecting and critical thinking. In general, this study emphasizes the needs of creative and innovative instructional strategies, a supportive and inclusive learning environment, and purposeful assessment to improve students’ speaking skills in EFL context of higher education. Future studies are recommended to evaluate the long-term effects of these strategies over various cultural settings.